2013
DOI: 10.1063/1.4802497
|View full text |Cite
|
Sign up to set email alerts
|

The nature of chemical reaction-driven tip-streaming

Abstract: The discovery of chemical reaction-driven tip-streaming (also known as "an amazing drop") was made about a decade ago during measurements of the dynamic interfacial tension of a water-alkali pendant droplet immersed in oil-linoleic acid. A plausible explanation for this self-sustained ejection of micron sized droplets from the tip of the macroscopic pendant drop was offered at that time and attributed to Marangoni stresses driving the reaction-produced surfactant along the interface. Later, asymptotic theory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…The majority of literature reports on similar systems that invoke interfacial reactions between surface active acid/base pairs suggest the cause is due to the ultra-low surface tension of these systems coupled with induced Marangoni stresses that can result in a self sustaining stream of droplets from the interfacial region. [34][35][36][37][38] For a typical preformed emulsifier, in the absence of droplet breakup, the newly generated oil-water interface becomes saturated with surfactant by first, diffusion of surfactant molecules from the bulk continuous phase to the interfacial region, and second, by adsorption of the surfactant from this region to the oil-water interface. The equilibrium adsorption is determined by the rate of adsorption of monomeric surfactant units from the interfacial region and the rate of desorption from the interface (see Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of literature reports on similar systems that invoke interfacial reactions between surface active acid/base pairs suggest the cause is due to the ultra-low surface tension of these systems coupled with induced Marangoni stresses that can result in a self sustaining stream of droplets from the interfacial region. [34][35][36][37][38] For a typical preformed emulsifier, in the absence of droplet breakup, the newly generated oil-water interface becomes saturated with surfactant by first, diffusion of surfactant molecules from the bulk continuous phase to the interfacial region, and second, by adsorption of the surfactant from this region to the oil-water interface. The equilibrium adsorption is determined by the rate of adsorption of monomeric surfactant units from the interfacial region and the rate of desorption from the interface (see Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…2(a), self-driven Marangoni singularities have not been thoroughly studied. Marangoni-driven flows exhibiting interfacial singularities, which motivated the present study, were found experimentally only recently [19,[36][37][38][39] and are shown in Figs. 2(b) and 2(c).…”
mentioning
confidence: 94%
“…(7) Let us identify the conditions under which a solution local near a cusp singularity exists in the Stokes approximation. The corresponding stream function (6) satisfies the kinematic boundary condition (3) provided [17,35] -viscous stresses in the surrounding phase deform the drop, which forms pointed ends; (b) chemical reaction-driven tip streaming [19,36,37] -the acid-base chemical reaction at the water-oil interface produces a surfactant, which drives the Marangoni flow along the interface leading to a conical shape of the drop with a singular cone tip', (c) surfactant-driven fingering [38,39]-soapy water displaces air in the narrow space between two glass plates (Hele-Shaw cell) and eventually leads to fingering with cusps between the fingers. 043019-2 CUSPS AND CUSPIDAL EDGES AT FLUID INTERFACES: ... which allows us to rewrite the formula (6) as…”
mentioning
confidence: 99%
“…[6][7][8] The goal is to Such temporal and spatial gradients can be created through various physical or chemical processes, including inhomogeneous mixing, solubilization or miscellization of surfactants adsorbed on the drop surface, and chemical reactions of the drop. [21][22][23] The resulting surface tension gradient can then reconfigure the drop morphology and induce complex internal, interfacial, and external flows. [24,25] The induced external flow may, in turn, drive the motion of the drop.…”
Section: Introductionmentioning
confidence: 99%